V(D)J Rearrangement Is Dispensable for Producing CDR-H3 Sequence Diversity in a Gene Converting Species - Leighton, Philip A.; Morales, Jacqueline; Harriman, William D.; Ching, Kathryn H. (Frontiers in Immunology, 2018)
An important characteristic of chickens is that the antibody repertoire is based on a single framework, with diversity found mainly in the CDRs of the light and heavy chain variable regions. Despite this apparent limitation in the antibody repertoire, high-affinity antibodies can be raised to a wide variety of targets, including those that are highly conserved. Transgenic chickens have previously been generated that express a humanized antibody repertoire, with a single framework that incorporates diversity by the process of gene conversion, as in wild-type chickens. Here, we compare the sequences and antibodies that are generated purely by gene conversion/somatic hypermutation of a pre-rearranged heavy chain, with the diversity obtained by V(D)J rearrangement followed by gene conversion and somatic hypermutation. In a gene converting species, CDR-H3 lengths are more variable with V(D)J rearrangement, but similar levels of amino acid diversity are obtainable with gene conversion/somatic hypermutation alone.